Assessing the Potential Diagnostic Value of Indonesian Local Allergen Skin Prick Testing (SPT) for Cow’s Milk Allergy among Atopic Dermatitis Patients - Anggraeni, Sylvia; Damayanti; Umborowati, Menul Ayu; Prakoeswa, Cita Rosita Sigit (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Atopic dermatitis (AD) is a multifactorial chronic, frequently recurrent, inflammatory skin condition. The development of IgE-mediated food allergies and food sensitivity are both associated with atopic dermatitis. Cow’s milk allergy (CMA) caused the most common hypersensitivity reaction during childhood; however, the prevalence in adults is around 0.5%. Patients with AD use the Skin Prick Test (SPT) to evaluate the specific sensitization process. Purpose: This study aimed to assess cow's milk allergy among adult AD patients using local allergen extract SPT, standard SPT, and specific IgE (sIgE), as well as evaluating the conformity and relevance of the test results. Methods: Using consecutive sampling technique, the study was conducted twice on 45 adult AD patients with a one-week interval between administrations. Result: Local cow's milk SPT showed 4 positive results, and standard SPT showed 5. No sIgE test was positive. Local SPT was negative for 86.67% of individuals without a history of suspected cow's milk allergies. Standard SPT results were positive for 2.22% of individuals with a history of suspected cow's milk allergies and negative for 86.67% of those without. The relevance between local and standard SPT was shown to be substantial (k = 0.384, p = 0.000). Conclusion: The result of the local cow’s milk SPT and the patient’s history had good conformity, and the relevance with standard SPT was significant in diagnosing cow’s milk allergy among AD patients.